2023
DOI: 10.3390/ijerph20032261
|View full text |Cite
|
Sign up to set email alerts
|

Can an Aerobic Exercise Programme Improve the Response of the Growth Hormone in Fibromyalgia Patients? A Randomised Controlled Trial

Abstract: Downgrade alterations in the growth hormone (GH) might be involved in the development of some of the fibromyalgia syndrome (FMS) symptoms. Our aim was to assess the effects of an aerobic exercise programme on the GH levels in patients with FMS. A randomised controlled trial was developed. Sixty-four Spanish women with FMS were randomly assigned to the experimental arm (n = 33) and treated with a 16-week group physical exercise programme based on low impact aerobic dance (three weekly sessions, one-hour each), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…IGF-1 level is an indicator of GH secretion. Symptoms such as lack of energy seen in deficiency of GH in adults, poor general health, reduced exercise capacity, muscle weakness, cold intolerance, and impaired cognitive functions are similar to the symptoms described in FMS patients 4 – 8 . It is stated that the levels of leptin and growth factors (IGF-1 and insulin-like growth factor binding protein-3 (IGFBP-3)) vary in patients with fibromyalgia and this is a negative factor for homeostasis of the hypothalamic-pituitary-adrenal axis and skeletal muscle 5 .…”
Section: Introductionmentioning
confidence: 69%
“…IGF-1 level is an indicator of GH secretion. Symptoms such as lack of energy seen in deficiency of GH in adults, poor general health, reduced exercise capacity, muscle weakness, cold intolerance, and impaired cognitive functions are similar to the symptoms described in FMS patients 4 – 8 . It is stated that the levels of leptin and growth factors (IGF-1 and insulin-like growth factor binding protein-3 (IGFBP-3)) vary in patients with fibromyalgia and this is a negative factor for homeostasis of the hypothalamic-pituitary-adrenal axis and skeletal muscle 5 .…”
Section: Introductionmentioning
confidence: 69%
“…Exercise therapy has been shown to improve symptoms of FM through various mechanisms. A trial found moderate effects of a 16-week physical exercise program on aerobic exercise in improving the growth hormone response, suggesting the possible role of aerobic exercise in endocrinological modulation (30). After aerobic exercise, resistance training (RT) is the most common modality of exercise.…”
Section: Non-pharmacological Therapymentioning
confidence: 99%
“…Some of the main advantages of PEBT are that it is an active and ludic therapy that can be performed in groups and that can increase social support between patients with FMS. Pilates ( Franco et al, 2023 ), dance ( Murillo-Garcia et al, 2022 ), yoga ( Allsop et al, 2022 ), tai chi ( Cheng et al, 2019 ), circuit training (aerobic, strength and multicomponent) ( Vilarino et al, 2021 ; Araya-Quintanilla et al, 2022 ; Estrada-Marcén et al, 2023 ), body awareness therapy ( Bravo et al, 2019 ), and videogames ( Cortés-Pérez et al, 2021 ) are the most common forms to peform PEBT in patients with FMS; the effects of these forms of therapy have been widely assessed in the scientific literature, and promising results have been obtained.…”
Section: Introductionmentioning
confidence: 99%